Pharmacological antagonism of Anchietia salutaris extracts on the contraction induced by prostaglandin D2 and U46619 in guinea-pig lung parenchymal strips - Gambero, Alessandra [UNESP]; Gomes, José Carlos [UNESP] (My University, 1998)
Anchietia salutaris tea is traditionally used in Brazil to treat allergies, suggesting it contains compounds with antagonistic activity on the allergic mediators. We have evaluated extracts and semi-purified fractions of Anchietia salutaris as a source of compounds having this type of antagonism on the contraction induced in guinea-pig lung parenchymal strips and on platelet aggregation and shape change. After 10 min pre-incubation dichloromethane extracts containing 30 or 100 μg mL-1 inhibited the contraction induced by prostaglandin D2 (PGD2) in guinea-pig lung parenchymal strips with dose ratios (DR) of 0.76 ± 0.14 and 0.93 ± 0.19, respectively; the amount of inhibition depended both on the concentration and on the time of preincubation (DR after 30 min pre-incubation was 1.21 ± 0.51). The dichloromethane extract and its semi-purified fractions also inhibited the contractions induced by U46619, a more potent, stable, synthetic agonist of thromboxane A2 (TxA2) prostanoid (TP) receptors, the receptors acted upon by PGD2 to produce lung contractions. The dichloromethane extract did not inhibit the lung parenchymal contractions induced by histamine, leukotriene D4 (LTD4) or platelet-activating factor (PAF). Platelet aggregation induced by U46619, adenosine 5'-diphosphate (ADP) or PAF was not inhibited by the dichloromethane extract. Indeed, the extract potentiated platelet aggregation induced by low concentrations of these agonists and also potentiated the shape change induced by U46619. These results imply that the dichloromethane extract of Anchietia salutaris and its semipurified fractions contain an active principle that competitively inhibits TxA2 TP receptors, the stimulation of which causes lung parenchymal contraction. The inhibition seems to be selective for this receptor subtype, because the extract fails to inhibit platelet aggregation or shape change. This provides additional support of earlier reports suggesting the occurrence of TP receptor subtypes.
Keywords: 15 hydroxy 11alpha,9alpha epoxymethanoprosta 5,13 dienoic acid; dichloromethane; histamine; leukotriene d4; plant extract; prostaglandin d2; prostanoid receptor; thrombocyte activating factor; thromboxane a2; animal tissue; drug antagonism; female; guinea pig; male; nonhuman; thrombocyte aggregation; thrombocyte shape; 15-Hydroxy-11 alpha,9 alpha-(epoxymethano)prosta-5,13-dienoic Acid; Animals; Drug Interactions; Female; Guinea Pigs; Lung; Male; Muscle Contraction; Muscle, Smooth; Plant Extracts; Plants, Medicinal; Platelet Aggregation; Prostaglandin D2; Receptors, Thromboxane